A Literature Study on Polygamy Practices in the Context of Islamic Law and Indonesian Legal Framework - L. Sukrizal Watoni (Journal of Islamic Religious Studies, 2025)
Polygamy remains a complex and contested issue in Indonesia, where Islamic legal norms intersect with national regulations, particularly Law No. 1 of 1974 on Marriage and the Compilation of Islamic Law (KHI). This study aims to explore how polygamy is conceptualized in Islamic jurisprudence and Indonesian statutory law, identify the gaps between legal norms and practical implementation, and evaluate opportunities for legal harmonization and gender justice. Employing a qualitative literature study approach, this research systematically analyzed scholarly publications, legal documents, and comparative texts from 2015 to 2024 using purposive sampling. Data were examined through content analysis and legal hermeneutics, focusing on themes such as legal requirements, women’s rights, and socio-legal implications. The findings reveal that while both Islamic law and Indonesian legislation formally permit polygamy under specific conditions—such as fairness and financial capacity—many real-world practices, including unregistered (sirri) polygamous marriages, occur outside legal oversight, leaving women and children vulnerable. The study also highlights the gender asymmetry embedded in current laws, which grant polygamous rights exclusively to men. Comparative insights from countries like Morocco illustrate more progressive alternatives, such as prenuptial conditions limiting polygamy. This research underscores the need for legal reform and reinterpretation of Islamic law in alignment with principles of justice and gender equality. The study contributes to ongoing discourse on Islamic family law, legal pluralism, and human rights in Indonesia.